(untitled) (Research, Society and Development, 2026)
The increasing demand for orofacial harmonization procedures, driven by aesthetic standards disseminated through social media, has highlighted its association with Body Dysmorphic Disorder (BDD), a condition characterized by excessive concern with perceived physical flaws and persistent dissatisfaction. This study aimed to analyze the relationship between BDD and the search for facial aesthetic procedures, as well as the responsibility of dental professionals in such cases. This is a qualitative and descriptive literature review conducted in the SciELO, PubMed, Virtual Health Library, and Google Scholar databases, including publications from 2013 to 2026. After applying eligibility criteria, 17 articles were included in the final sample. The findings indicate that the prevalence of BDD is significantly higher among patients seeking facial aesthetic procedures, reaching up to twenty times that of the general population. These individuals present distorted self-image and repeatedly undergo interventions without achieving lasting satisfaction, since the disorder has a psychological origin. It is concluded that facial harmonization may represent an iatrogenic risk in patients with BDD, making early identification, prior psychological assessment, and ethical conduct by dental professionals essential, prioritizing mental health and comprehensive patient care.